Persebaran Subjek Artikel-Artikel Jurnal Tik Ilmeu 2017-2022 - Syarifudin, Faisal (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
This study aims to discover subject dispersion of Tik Ilmeu journal articles. Research data were generated from 86 articles of 2017-2022 publication. The subjects were assigned through analysis of the titles, abstracts and keywords. Subjects were grouped according to the JITA Classification System of Library and Information Science. During six years publication, subjects that received high attention, namely Information sources, supports, channels 15 times (17%), followed by Â Users, literacy and reading 14 times (16%), then by Information technology & library technology 13 times (15%). Information treatment for information services published 3 times (4%), Theoretical and general aspects of lib & Info, and Industry, profession and education, both 4 times (5%), Publishing and legal issues and Housing technologies only 1 (1%) in the same period. Both subjects were ignored by the authors for 5 years. From year to year, Information sources, supports, channels was consistently represented and get the most attention. Information technology & library technology, despite their high percentage, was not represented in the first year. This subject reached its highest peak in 2019 (36%) then fell, and at the end of the period it was only 12%.Â